Effects on animal tumors and toxicity of lycobetaine acetate - Zhang Su-yin; Lu Fei-li; Yang Jin-long; Wang Long-jiang; Xu Bin (Acta Pharmacologica Sinica, 2016)
Lycobetaine, a derivative of lycorine, is a new type of antitumor drug. When lycobetaine acetate (AT-1840) was given ip to mice and rats inoculated with Ehrlich ascites carcinoma, ascites hepatoma, leukemia L-1210, leukemia P-388, Lewis lung cardinoma or Yoshida ascites sarcoma, the survival times of the tumor-bearing animals were prolonged significantly. Lycorine exhibited only negligible effect on the above-mentioned tumors. The acute ip LD50 of AT-1840 in mice was 72 mg/kg. In dogs iv 3 or 9 mg/kg of AT-1840 once every other day for 7 times produced no apparent toxic action except mild leucopenia and thrombopenia in the group of large dosage. It seems that the presence of phenolic betaine in the molecule of AT-1840 bears some relationship to its antitumor activity. AT-1840 has been recommended for clinical trials.